Clinico-epidemiological characteristics of Kawasaki-like disease in paediatric patients with COVID-19: a protocol for rapid living systematic review - Sanghamitra Pati; Abhinav Sinha; Swetalina Nayak; Priyadarshini Dehuri; Srikanta Kanungo (BMJ Open)
Introduction The COVID-19 outbreak has posed a major challenge to healthcare providers. Due to its communicable nature, very stringent public health interventions have been put in place worldwide; yet, it still poses new emerging challenges, one of the most recent being a multisystem inflammatory condition with clinical features resembling Kawasaki-like disease and toxic shock syndrome in children and adolescents. The data on this novel condition are scarce which need to be reported to identify its clinico-epidemiological and geographical distribution. There is an urgent need to generate evidence for diagnosis and management of this condition in the midst of a pandemic.Methods and analysis This systematic review will be conducted using Medline database searched through PubMed, Embase, Ovid; and Google Scholar, ProQuest and EBSCO databases will also be searched along with grey literature with the aim to identify the clinical features, aetiopathology, laboratory findings, treatment modes and outcomes of Kawasaki-like disease among paediatric patients suffering from COVID-19. Original articles reporting Kawasaki-like disease in paediatric patients with COVID-19 will be retrieved after screening by two independent reviewers. Data will be extracted in a specially designed form and studies will be assessed independently for risk of bias. Data will be extracted for the following: author, journal title, publication year, study design, study setting, demographic characteristics, sample size, clinical features, aetiopathology, laboratory findings, modes and doses of treatment given, strength and weakness of studies. A descriptive and quantitative analysis will be completed.Ethics and dissemination This is a literature-based review study with no ethical concerns. We will publish the results in a peer-reviewed journal and present at a conference.PROSPERO registration number CRD42020187427.